Different Signs: Generational Variations, an analysis of the external social factors in ÍTM - Christine Heirbaut 1984- (2022)
Icelandic Sign Language (ÍTM), like other sign languages, has sociolinguistic and lexical variations. Changes in school policy can have a significant impact on both the use and acquisition of sign language, resulting in generational differences. To gain a better understanding of the reasons for these language variations, we reviewed the history of Deaf education in Iceland as well as the various language policies that had been implemented. We examined various social factors such as the signer's region of origin, age, ethnicity, and gender, and determined that the signers' age and educational background are most likely the driving factors behind the variations in ÍTM. This study looked at two distinct groups of vocabulary that are unrelated to one another: devices or appliances and foods. The analysis of interviews with 14 Deaf individuals, ranging in age from 24 to 59, reveals that there are numerous lexical variations in ÍTM. We divided the participants into three different groups based on the language policy that was in place during their school years. Within the word category of appliances, few lexical variations were observed whereas phonological variations appeared to be quite common. In this category, signers of all ages have largely adopted the same signs. While there appear to be numerous lexical variations in the food category, a number of signs were commonly used, primarily by the younger group of participants, such as SAMLOKA (sandwich), PÍTSA (pizza), BROKKOLÍ (broccoli) and PERA (pear). In the vast majority of cases no noticeable lexical variation could be linked to a specific age group. Íslenskt táknmál (ÍTM) hefur, eins og önnur táknmál, mjög mikinn breytileika, bæði hvað varðar félagsmálfræði og orðasafn. Breytingar á skólastefnu geta haft veruleg áhrif bæði á notkun og tileinkun táknmála þannig að kynslóðamunur verður til. Til þess að öðlast betri skilning á ástæðum þessara tungumálabreytileika er farið yfir sögu menntastefnu heyrnarlausra á Íslandi sem og hinar mismunandi málstefnur sem ...